Evaluation of fibromyalgia syndrome in patients with rosacea - Emine Müge ACAR; Hilal KAYA ERDOĞAN; Senem ŞAŞ; Ersoy ACER (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the frequency of fibromyalgia syndrome (FMS) in rosacea patients and the relationship between disease disability score of FMS and quality of life score of rosacea. Patients and methods: This cross-sectional controlled clinical trial was performed between December 2017 and December 2018. One hundred female rosacea patients (mean age 43.2±10.1; range, 21 to 65 years) and 100 age- and sex-matched control subjects (mean age 41.2±11.1; range, 22 to 68 years) with no history of skin disease and systemic diseases including diabetes, cardiovascular, renal and hepatic diseases were recruited. Dermatology Life Quality Index (DLQI) scores were calculated using a 10-item self-administered questionnaire. The diagnosis of FMS was established according to 2010 American College of Rheumatology diagnostic criteria. Fibromyalgia Impact Questionnaire (FIQ) was used to determine the clinical severity and functional disability, while Visual Analog Scale (VAS) was used to determine pain severity in the patients with FMS. Results: The frequency of FMS in patient group was significantly higher than control group (p=0.019). The mean duration of FMS in patient group was significantly higher than control group (p=0.001). There was no significant difference in terms of the age of onset of FMS, FIQ and VAS scores between groups (p=0.53, p=0.54, p=0.07, respectively). DLQI scores were significantly correlated with FIQ scores in the patient group (r=0.43, p=0.008). Conclusion: The frequency of FMS in rosacea patients was significantly higher than control subjects without any skin disease and there was a correlation between disability score of FMS and quality of life score of rosacea. Investigating fibromyalgia symptoms in rosacea patients may be helpful for providing patient-based therapeutic approaches where neurologically based treatments may also be beneficial for rosacea.